2022
DOI: 10.1038/s41429-022-00514-w
|View full text |Cite
|
Sign up to set email alerts
|

Azepanodipterocarpol is potential candidate for inhibits influenza H1N1 type among other lupane, oleanane, and dammarane A-ring amino-triterpenoids

Abstract: A series of lupane-, oleanane-and dammarane-based triterpenoids with 3β-amino, A-ring azepano-and 3,4-seco-fragments has been synthesized and evaluated for antiviral activity against influenza A(H1N1) virus. It was found that azepanodipterocarpol 8 and 3β-amino-28-oxoallobetulin 11 showed antiviral activity with IC 50 1.1 and 2.6 μg ml −1 , and selectivity index of 19 and 10, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Thus, gomopiperazine amide 2 with IC 50 of 21 µM and SI > 27 was established as the most active compound in this series, which is consistent with the data, demonstrating that triterpenoids derivatives with cyclic amide moieties had the highest antiviral activity [ 46 ]. Previously, we have found that methyl 3 β -amino-oleanoate 21 has antiviral activity with an IC 50 of 7.9 μM, but a higher CC 50 of 18 μM which led to lowering the selectivity index (SI 2) [ 47 ]. The esterification of methyl 3 β -amino-oleanoate 21 with phthalic anhydride resulted increased activity (IC 50 of 12 μM), but significantly lower toxicity (CC 50 > 486 μM) in compound 22 , resulting in a selectivity index of >42.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, gomopiperazine amide 2 with IC 50 of 21 µM and SI > 27 was established as the most active compound in this series, which is consistent with the data, demonstrating that triterpenoids derivatives with cyclic amide moieties had the highest antiviral activity [ 46 ]. Previously, we have found that methyl 3 β -amino-oleanoate 21 has antiviral activity with an IC 50 of 7.9 μM, but a higher CC 50 of 18 μM which led to lowering the selectivity index (SI 2) [ 47 ]. The esterification of methyl 3 β -amino-oleanoate 21 with phthalic anhydride resulted increased activity (IC 50 of 12 μM), but significantly lower toxicity (CC 50 > 486 μM) in compound 22 , resulting in a selectivity index of >42.…”
Section: Resultsmentioning
confidence: 99%
“…Their activity toward a broad spectrum of viruses is known, including herpes, papilloma, human immunodeficiency, hepatitis, influenza viruses, SARS‐CoV‐2, cytomegalovirus, etc. (Babaev et al., 2022; Kazakova, Tret'yakova, & Baev, 2021; Liu, Yang, Wang & Xiong, 2022; Smirnova et al., 2022; Wu et al., 2020; Ye et al., 2021; Yi et al., 2022). The antiviral effect of these compounds is due to several types of activity including direct antiviral action, effects on cellular antiviral pathways, and immunomodulatory activity, in particular, activation of the nonspecific immunity system (Li, Sun, Xiao, Zhang & Zhou, 2020; Xiao et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Data on the synthesis conditions and properties of the obtained polymers are summarized in Table 1. The cytotoxic and antiviral properties of polymers were evaluated in vitro as described in [10].…”
mentioning
confidence: 99%